Overtourism as destination risk : impacts and solutions - Sharma, Anukrati; Hassan, Azizul (Tourism security-safety and post conflict destinations, 2021)
The tourism industry provides a vital lifeline in helping to develop and enhance the economic growth of cities, states, and nations, but there is growing concern internationally about how overtourism in certain regions is having an adverse impact on a number of tourist destinations. Overtourism as Destination Risk: Impacts and Solutions presents a range of researcher perspectives discussing current issues in the overtourism debate, including unplanned expansion and construction, environmental imbalance and damage, pollution and deforestation, as well as measures and possible solutions to tackle the problem of overtourism and its spread. This book specifically focuses on Coimbra in Portugal, Amsterdam in the Netherlands and Shimla in India. This book foregrounds the tourist's responsibility to respect destinations and provides an in-depth assessment of possible risk factors and the conflicted role of the media and marketing organizations as image-makers of tourist destinations. This book is essential reading for academics and researchers from the fields of tourism studies, social sciences, environmental sciences, humanities and relevant disciplines.